2011
DOI: 10.1177/0022167811422947
|View full text |Cite
|
Sign up to set email alerts
|

An Existential–Integrative Treatment of Anxious and Depressed Adolescents

Abstract: Today’s generation of young clinicians appear unfamiliar with how to incorporate existential concepts when treating adolescents experiencing internalizing symptoms. Empirically validated treatments for this population, including cognitive–behavioral, interpersonal, and psychopharmacological approaches undoubtedly are clearly beneficial. Several core existential concepts, however, can be effectively integrated with these empirically supported treatments to enhance outcomes. The article begins with a discussion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 57 publications
0
19
0
Order By: Relevance
“…Many adolescents and young adults report EA and benefit from discussing this aspect of their lives in counseling (Shumaker, 2012). Prior research has looked at the impact of spirituality (Davis, Kerr, & Robinson-Kurpius, 2003), coping and social support (Mahmoud, Staten, Lennie, & Hall, 2015), humility (Kesebir, 2014), and natural disasters (Scott & Weems, 2013) on the experience of EA in young adults.…”
Section: Introductionmentioning
confidence: 99%
“…Many adolescents and young adults report EA and benefit from discussing this aspect of their lives in counseling (Shumaker, 2012). Prior research has looked at the impact of spirituality (Davis, Kerr, & Robinson-Kurpius, 2003), coping and social support (Mahmoud, Staten, Lennie, & Hall, 2015), humility (Kesebir, 2014), and natural disasters (Scott & Weems, 2013) on the experience of EA in young adults.…”
Section: Introductionmentioning
confidence: 99%
“…A salient concern that may be precipitated by traumatic stress exposure is existential anxiety, which involves apprehension about the ultimate meaning of life and death (Tillich, 1952, 1961). Existential concerns are a core human issue in a great deal of theoretical and philosophical writing (e.g., Kierkegaard, 1843/1954; Sartre, 1957; Tillich, 1952, 1961; see Shumaker, 2011; Weems & Berman, 2012, for reviews). Previous research has demonstrated that existential concerns are related to a number of emotional problems (e.g., Baldwin & Wesley, 1996; Chung, Chung, & Easthope, 2000; Martz, 2004; Mascaro & Rosen, 2006; Weems, Costa, Dehorn, & Berman, 2004).…”
mentioning
confidence: 99%
“…99-100). Furthermore, more recently, Shumaker (2012) discussed the general relevance of the “hero” metaphor in therapeutic practice with adolescent clients but did not provide a specific practical strategy. Meantime, no research has been conducted that formally appraised the effectiveness of these techniques.…”
Section: Personal Hero Identification As a Therapeutic Techniquementioning
confidence: 99%
“…Further case studies and qualitative analyses are warranted to provide additional empirical support for the PHT. For instance, they could demonstrate its effectiveness with a variety of populations, especially: (a) adolescents, given the aforementioned relevance of hero metaphors at that developmental phase (Constantino et al, 1988; Shumaker, 2012) as identity is negotiated (Erikson, 1959/1994); (b) emerging adults (a developmental phase peculiar to developed societies characterized by simultaneous excitement about possibilities and worry about one’s future and by increased well-being for some but more intense anxiety/depression for others, see Arnett, 2000; Schwartz, 2016); and (c) individuals negotiating crises of self during adulthood (see Robinson & Smith, 2010) to supplement the two accounts presented above. The suitability of the PHT in a variety of settings (including not only therapeutic but also educational, which I did not cover in this article due to space constraints) also should be demonstrated.…”
Section: Suggestions For Future Researchmentioning
confidence: 99%